2019
DOI: 10.3389/fmed.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Melanocortin Receptors and Their Agonists in Pulmonary Disease

Abstract: Melanocortin agonists are ancient neuropeptides that have steroidogenesis and anti-inflammatory properties. They activate melanocortin receptors (MCR), a family of five seven-transmembrane G-protein coupled receptors. MC1R and MC3R are mainly involved in immunomodulatory effects. Adrenocorticotropin hormone (ACTH) and alpha-Melanocortin stimulating hormone (α-MSH) reduce pro-inflammatory cytokines in several pulmonary inflammatory disorders including asthma, sarcoidosis, and the acute respiratory distress synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 72 publications
(76 reference statements)
0
36
0
Order By: Relevance
“…As aforementioned, this mutation is linked with obesity in human but equally it has been shown that the interaction between MC3R and its ligand α-melanocyte stimulating hormone (α-MSH) suppressed dermatitis in a mouse model of atopic dermatitis. Even more, α-MSH reduced eosinophil counts, serum levels of IgE, IL-4 and IL-5 in asthmatic mice (10). Their study suggests MC3R activity has an anti-TH2 effect and an abrogation (mutation) of this gene may have caused atopic dermatitis in our patient.…”
Section: Case Reportmentioning
confidence: 53%
“…As aforementioned, this mutation is linked with obesity in human but equally it has been shown that the interaction between MC3R and its ligand α-melanocyte stimulating hormone (α-MSH) suppressed dermatitis in a mouse model of atopic dermatitis. Even more, α-MSH reduced eosinophil counts, serum levels of IgE, IL-4 and IL-5 in asthmatic mice (10). Their study suggests MC3R activity has an anti-TH2 effect and an abrogation (mutation) of this gene may have caused atopic dermatitis in our patient.…”
Section: Case Reportmentioning
confidence: 53%
“…Here, we used ACTH to interrogate the role of MCRs in the immune response, as we strove to identify an alternative signaling pathway for the delivery of immunosuppression following heart transplantation. Lymphocytes have been reported to express MC1R, MC3R, and MC5R (26,27,49,(87)(88)(89)(90). However, the expression of MC2R by lymphocytes has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the melanocortin system with natural or synthetic ligands exerts beneficial effects in acute, chronic, and systemic inflammatory disorders ( 25 27 , 48 , 49 , 77 ). Moreover, different clinical studies have investigated efficacy of ACTH and NDP- α -MSH therapies in systemic inflammatory diseases, including ARDS, rheumatoid arthritis, multiple sclerosis (MS), lupus erythematosus (SLE), kidney diseases, and nephrotic syndromes ( 70 72 ).…”
Section: The Melanocortin System: a Potent Endogenous Modulatory Pathmentioning
confidence: 99%
“…Melanocortins exert marked anti-inflammatory and immunomodulatory influences. Physiological role and effectiveness in treatment of acute, chronic, and systemic inflammatory disorders are well-documented (25)(26)(27)(28). Exploiting the melanocortin system could form a realistic basis to counteract certain deleterious effects of respiratory viruses not only for the present but also for possible future pandemics.…”
Section: Introductionmentioning
confidence: 99%